Morality and religion in African thought - P. J. Nel (Acta Theologica)
The article deals critically with current discourses on morality in African thought. These discourses reflect the ambivalence between those scholars seeking to define African morality within the parameters of a conventionalised, Western, religious episteme, and those pursuing an “Africanist” (Afrocentric) explanation which embraces an authentic mode of African knowledge construction within indigenous communities. The assumption that faith or religion is the foundation of African morality can only be partially endorsed when one grants space for hybrid moral constructions between Christianity and indigenous religion. However, African morality is not necessarily based on religion or faith, but on the beneficiary values of collective family and community well-being, without dissolving the individual’s character. In African thought, the “best” rational justification of the moral imperative is less of an issue than in current moral discourse.